Essays on corporate restructuring - Brunassi Silva, Vinicius Augusto (2015)
This thesis examines the characteristics of the decision-making process of creditors with respect to either pursuing court reorganization or bankruptcy. It is divided into four chapters, which have been written as stand-alone papers. The second chapter provides a general review of the theoretical and empirical papers on reorganization and bankruptcy. It also describes three case studies to show the complexity of each case in terms of the concentration of claims, disparities of interest among the three classes of creditors and the final decision regarding the approval or rejection of the reorganization plan. The third chapter studies the determinants of delay in corporate reorganizations. It empirically investigates delays in voting on reorganization plans between 2005 and 2014, suggesting that (i) a high concentration of debt among classes of claimholders is related to shorter delays; (ii) a higher number of banks holding claims is related to longer delays; (iii) the average delay decreases considerably when only one class is voting on the plan; (iv) labor and secured creditors demand a delay when the level of collateral is higher; (v) the average delay is longer when the performance of the debtor’s sector is lower and the delay is demanded by secured or unsecured classes; and (vi) a divestment proposal is the main topic discussed by claimholders in cases with longer delays. The fourth chapter presents evidence on the approval of the reorganization plan. To the best of our knowledge, this is the first study to analyze the likelihood of approval based on reorganization plans for creditors that require approval by employees and secure and unsecure debtholders. We find that (i) the labor class of creditors is likely to approve the reorganization plan even when the plan is rejected, (ii) plans with more heterogeneous payment for classes are less likely to be accepted, (iii) plans are less likely to be accepted when there are more unsecure creditors and (iv) plans with divestment proposals are more likely to be accepted. Finally, as expected given the seniority position of secured debt, plans are less likely to be accepted when the portion of secured debt is higher, and the reverse is true for unsecured debt.